Dysregulated Microglial Cell Activation and Proliferation Following Repeated Antigen Stimulation - Prasad, Sujata; Sheng, Wen S.; Hu, Shuxian; Chauhan, Priyanka; Lokensgard, James R. (Frontiers in Cellular Neuroscience, 2021)
Upon reactivation of quiescent neurotropic viruses, (Ag)-specific brain resident-memory CD8+ T-cells (bTRM) may respond to de novo-produced viral Ag through rapid release of IFN-γ, which drives subsequent interferon-stimulated gene expression in surrounding microglia. Through this mechanism, a small number of adaptive bTRM may amplify responses to viral reactivation leading to an organ-wide innate protective state. Over time, this brain-wide innate immune activation likely has cumulative neurotoxic and neurocognitive consequences. We have previously shown that HIV-1 p24 antigen (Ag)-specific bTRM persist within the murine brain using a heterologous prime-CNS boost strategy. In response to Ag re-challenge, these bTRM display rapid and robust recall responses, which subsequently activate glial cells. In this study, we hypothesized that repeated recall responses to viral Ag (modeling repeated episodes of viral reactivation) culminate in prolonged reactive gliosis and exacerbated neurotoxicity. To address this question, mice were first immunized with adenovirus vectors expressing the HIV p24 capsid protein, followed by a CNS-boost using Pr55Gag/Env virus like particles (HIV-VLPs). Following establishment of the bTRM population (>30 d), prime-CNS boost animals were then subjected to in vivo recall stimulation, as well as restimulation (at 14 d post-recall stimulation), using the immunodominant HIV-1 AI9 CD8+ T-cell epitope peptide. In these studies, Ag restimulation resulted in prolonged expression of microglial activation markers and an increased proliferative response, longer than recall stimulation alone. This continued expression of MHCII and PD-L1 (activation markers), as well as Ki67 (proliferative marker) was observed at 7, 14, and 30 d post-AI9 restimulation. Additionally, in vivo restimulation resulted in continued production of inducible nitric oxide synthase (iNOS) with elevated levels observed at 7, 14, and 30 d post-restimulation. Interestingly, iNOS expression was significantly lower among recall-stimulated animals when compared to restimulated groups. Furthermore, in vivo specific Ag restimulation produced lower levels of arginase (Arg)-1 when compared with the recall-stimulated group. Taken together, these results indicate that repeated Ag-specific stimulation of adaptive immune responses leads to cumulative dysregulated microglial cell activation.